Mutant varicella-zoster virus thymidine kinase: correlation of clinical resistance and enzyme impairment. - Roberts, G B (1991)
Varicella-zoster virus (VZV) encodes a thymidine kinase (EC 2.7.2.21) which phosphorylates several antiviral nucleoside analogs, including acyclovir (ACV). A mutation in the VZV thymidine kinase coding sequence, resulting in an arginine-to-glutamine substitution at amino acid residue 130 (R130Q), is associated with clinical resistance to ACV. We have expressed the wild-type and the mutant enzymes in bacteria and have studied the kinetic characteristics of the purified enzymes. The arginine-to-glutamine substitution resulted in decreased catalytic activity and altered substrate specificity. The most striking effect was a decrease in the rates of nucleoside phosphorylation to less than 2% of the rates with the wild-type enzyme. This was accompanied by increased apparent Km values for thymidine and deoxycytidine. ACV was not detectably phosphorylated by the R130Q enzyme but still competed with thymidine for the enzyme. The inability of the R130Q enzyme to catalyze the phosphorylation of ACV correlates with resistance to ACV noted with a clinical isolate of VZV.